Arctic Environmental Test of Tactical Radio Communications Equipment - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1970)
The Environmental Test Procedure describes test methods and techniques for evaluating the performance and characteristics of tactical radio communications equipment under Arctic winter environmental conditions.